Locating The Poor: Spatial Poverty Mapping Of Household In Rajshahi City, Bangladesh - Moral, Md. Jahan Boksh (2011)
The main objectives of the study are to analyze the spatial poverty mapping of household, determine spatial infrastructure and services of the poor and to find out the association between vulnerability and poverty. The study also analyzes the application of logistic regression to determine the most influential indicators of poverty. The spatial and non-spatial information are used in the study which are assembled from the published documents, database of Rajshahi Development Authority (RDA) and field investigations using a structured questionnaire.